Identifikasi Material Yang Berpotensi Menjadi Waste Material Pada Proyek Gedung Kuliah Terpadu B Universitas Palangka Raya - Syahrial Al-Rasyid; Veronika Happy Puspasari (Jurnal Basement : Jurnal Teknik Sipil, 2024)
Construction projects are activities calculated to obtain maximum results in the form of buildings or infrastructure within limited time, costs and resources. Waste material in construction projects can result in material waste in construction project work. Therefore, it is necessary to identify materials that have the potential to cause waste material. This research aims to identify consumable materials in architectural work and the upper structure used which has a percentage of around (20%) which has value or has an impact of around (80%) on the construction of the Integrated Lecture Building B project at Palangka Raya University, Central Borneo. In this research, materials were identified in architectural work and upper structures that have the potential to cause material waste using the Pareto method (Pareto's law). The results of this research show the identification and grouping of material types that have the greatest rupiah value (80%) compared to other types of material and are materials that have the potential to cause material waste. The results obtained were 2 materials for upper structural work and 14 materials for architectural work. Accumulatively, the weight percentage required for the 2 materials in the upper structure work in this project is 72.25% compared to other types of upper structure materials. And the cumulative weight percentage required for the 14 materials in architectural work in this project is 79.43% compared to other types of architectural materials.